Major trends in human capital development in modern information technology market - A. R. Babayants; A. V. Zakharov (Вестник университета)
Digitalization as part of the trends of accelerating scientific and technological progress and transition to Industry 4.0 determines the need to pay increased attention to creating conditions for human capital development. Competition for human capital in a globalized market becomes similar to competition for other forms of capital and becomes global in nature. In such conditions, there is a growing need for business process owners to be aware of key trends in human capital development, distinctive features of labor market participants, and effective methods of its attraction. The subject of the study is the main trends in human capital development in the modern IT market, the purpose is to identify and systematize the manifestations of the IT market influence on the processes of human capital development and implementation. The research methodology includes the human capital development concepts, as well as the interpretation of analytical data on its development trends in the digital economy. The content analysis method, as well as the method of synthesis for formulating conclusions were applied. The main trends in human capital development in the modern IT market include a shift in emphasis towards soft skills, digital literacy as a universal competence, the active role of personnel in self-development, expansion of opportunities to acquire competencies (e-learning and digital universities), development of competencies within companies, and involvement of Generation Z representatives in labor relations. The scope of the obtained results application includes specialists of HR departments of IT companies, management, and authorities, whose sphere of activity includes the issues of human capital development.